h - Conrad, Eric; Seth Misenar; Joshua Feldman (Elsevier Science, 2016)
Eleventh Hour CISSP: Study Guide, Third Edition provides readers with a study guide on the most current version of the Certified Information Systems Security Professional exam. This book is streamlined to include only core certification information, and is presented for ease of last-minute studying. Main objectives of the exam are covered concisely with key concepts highlighted. The CISSP certification is the most prestigious, globally-recognized, vendor neutral exam for information security professionals. Over 100,000 professionals are certified worldwide, with many more joining their ranks. This new third edition is aligned to cover all of the material in the most current version of the exam's Common Body of Knowledge. All domains are covered as completely and concisely as possible, giving users the best possible chance of acing the exam. Completely updated for the most current version of the exam's Common Body of Knowledge Provides the only guide you need for last-minute studying Answers the toughest questions and highlights core topics Streamlined for maximum efficiency of study, making it ideal for professionals updating their certification or for those taking the test for the first time.
Vendor-supplied metadata.
Includes bibliographical references and index.
Keywords: Computer networks -- Security measures -- Examinations -- Study guides; Computer security -- Examinations -- Study guides; Telecommunications engineers -- Certification; Electrical engineering; Computer science; COMPUTERS / Security / General; COMPUTERS / Security / Networking; Computer networks -- Security measures -- Examinations; Computer science; Computer security -- Examinations; Electrical engineering; Telecommunications engineers -- Certification; Security; Study guides